« Ça ira plus vite comme ça » - Jean-Baptiste Devaux (Temporalités)
Technological policies aimed at bringing together scientific and economic actors underwent profound changes between 1962 and 1988. Technological policies in the form of “major technological programs” were succeeded by so-called “innovation support” policies, characterized in particular by investment support schemes for companies and the implementation of networks aimed at increasing synergies between the scientific and industrial worlds. This shift is accompanied by a reconfiguration of the temporalities of this sector of public action. The occasional character of the implementation of technological programs is replaced by a reform that we describe as permanent, essentially orchestrated by the Ministers of Industry. By focusing on the reforming work of four of them, we propose in this article to question the process of construction of an autonomous reform temporality. We first observe how these ministers desynchronize their activity from the temporalities imposed by administrative actors and the economic world. From the beginning of the 1970s, they fashioned a new reforming rhythm, synchronized with their own agenda and the temporalities of the political field.